Hybrid external fixation in the treatment of tibial pilon fractures: A retrospective analysis of 162 fractures. (October 2016) - Galante, Vito N.; Vicenti, Giovanni; Corina, Gianfranco; Mori, Claudio; Abate, Antonella; Picca, Girolamo; Conserva, Vito; Speciale, Domenico; Scialpi, Lorenzo; Tartaglia, Nicola; Caiaffa, Vincenzo; Moretti, Biagio
Abstract: Objectives: To determine the efficacy of hybrid external fixation in the treatment of tibial pilon fractures. Design: Retrospective, multicentre study. Patients/Participants: Adult patients with tibial pilon fractures treated with hybrid external fixation. Intervention: Fracture reduction with ligamentotaxis and fixation with XCaliber hybrid external fixator. Main outcome measurements: Fracture union, complications, functional outcome (Mazur Ankle Score). Results: Union was obtained in 159 fractures at an average of 125 days; there were three delayed unions and three non-unions. The most frequent complication was superficial pin‐track infections (48), all of which responded to local wound care and antibiotics. There were no deep infections and no DVT. Only one fracture had loss of reduction that required frame revision. The overall functional scores were 91 (excellent) for AO/OTA type A fractures, 89 (good) for type B fractures, and 75 (satisfactory) for type C fractures. Conclusions: Hybrid external fixation is an effective method of stabilising tibial pilon fractures, particularly those with marked comminution. The minimally‐invasive technique and stable fixation enable early mobilisation, with good functional results and minimal complications. Level of evidence: Level IV Case series.